2016
DOI: 10.1155/2016/2569732
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Role of Short-Term Volunteerism in International Development: Views from Volunteers, Local Hosts, and Community Members

Abstract: Background. Short-term international volunteer trips traditionally involve volunteers from high-income countries travelling to low- and middle-income countries to assist in service-related development activities. Their duration typically ranges from 7 to 90 days. The city of La Romana, Dominican Republic, receives hundreds of short-term international volunteers annually. They participate in activities aimed at improving conditions faced by a marginalized ethnic-Haitian community living in bateyes. Methods. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
(13 reference statements)
0
29
0
Order By: Relevance
“…They ask that their feedback be taken seriously by volunteers and volunteer organizations [ 23 25 , 27 , 31 ]. One study that surveyed VPO staff and community members in the Dominican Republic reported a “misalignment of the desired and actual skill sets of volunteers; duplicate and uncoordinated volunteer efforts; and the perpetuation of stereotypes suggesting that international volunteers possess superior knowledge or skills” [ 33 ]. Lasker identified “mutuality”, or the opportunity for all people involved to be learning and developing skills, as one of the most important principles for effective volunteering [ 2 ].…”
Section: Research Review Of Medical Volunteerism Practicesmentioning
confidence: 99%
“…They ask that their feedback be taken seriously by volunteers and volunteer organizations [ 23 25 , 27 , 31 ]. One study that surveyed VPO staff and community members in the Dominican Republic reported a “misalignment of the desired and actual skill sets of volunteers; duplicate and uncoordinated volunteer efforts; and the perpetuation of stereotypes suggesting that international volunteers possess superior knowledge or skills” [ 33 ]. Lasker identified “mutuality”, or the opportunity for all people involved to be learning and developing skills, as one of the most important principles for effective volunteering [ 2 ].…”
Section: Research Review Of Medical Volunteerism Practicesmentioning
confidence: 99%
“…This often results in host communities hosting separate, uncoordinated efforts that limits their overall scalability and impact. As an example, clinical STEGH are particularly vulnerable to such impacts on outputs and outcomes if local context and coordination is not considered; one study found that a hospital in the Dominican Republic welcomed STEGH on week to month-long experiences to perform everything from tubal ligation surgery, to dialysis services, to mobile primary clinics, to research and public health education [15].…”
Section: Towards An Outcomes-focused Approach In Steghmentioning
confidence: 99%
“…Nutrition advice is compromised because the food supply is inconsistent and parasites return, since shelter and hygiene remain inadequate. Escaping poverty remains difficult as entrenched economic and political systems limit job opportunities and community development; perhaps corrupt authorities even target this specific community because they know there are goods to be had-medicines and other charitable items left behind by the visiting team [15].…”
Section: What It Means: For Stegh and For Global Health And Developmentmentioning
confidence: 99%
“…Accepted principles of global health initiatives, especially those for student learners, began to emerge. These principles, which include early partnership between host and university personnel (Chavez et al, 2010;Middleton et al, 2014;Powell, Gilliss, Hewitt, & Flint, 2010), evidence of measurable sustainability goals (Loiseau et al, 2016;Melby et al, 2015) and rigorous predeployment orientation for students (Cherniak et al, 2017;Harrison, Logar, Le, & Glass, 2016), began to thread through global health curricula. From these principles, eight graduate-level learning domains were derived.…”
Section: Sugarman J and Working Group On Ethics Guidelines For Globalmentioning
confidence: 99%